How do you solve -7n - 2n = 5+ 1- n - 7n?

1 Answer
Oct 25, 2017

n=-6

Explanation:

I'll try to do it step by step

-7n-2n=5+1-n-7n

adding the n's and the numbers in each side

-9n=6-8n

the -8n goes to the other side as +8n

-9n+8n=6

then we add the n's in the left hand side

-n = 6

multiplying in both sides by (-1)

(-1)·(-n)=(-1)·6

and finally

n=-6

To prove we are right we change n into -6 in the original ecuation.

(-7)·(-6) - 2·(-6) =5+1 -(-6)-7·(-6)

and we get 36+12=6+6+36 => 48=48

Since we get the equalty is true, the answer is correct.